2022
DOI: 10.1002/prot.26438
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of tetrahydrocannabinol binding to the glycine receptor

Abstract: The recognition of Cannabis as a source of new compounds suitable for medical use has attracted strong interest from the scientific community in its research, and substantial progress has accumulated regarding cannabinoids' activity; however, a thorough description of their molecular mechanisms of action remains a task to complete. Highlighting their complex pharmacology, the list of cannabinoids' interactors has vastly expanded beyond the canonical cannabinoid receptors. Among those, we have focused our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…Further, the analysis of the ligand–receptor interaction appears somewhat limited, mentioning only the formation of a single hydrogen bond between THC and Ser296. Finally, it is worth noting that the orientation of THC proposed in this study differs from that observed in subsequent cryo-EM structures or more rigorous MD simulations …”
Section: Identification Of the Cannabinoid Binding Site And First Str...contrasting
confidence: 66%
See 4 more Smart Citations
“…Further, the analysis of the ligand–receptor interaction appears somewhat limited, mentioning only the formation of a single hydrogen bond between THC and Ser296. Finally, it is worth noting that the orientation of THC proposed in this study differs from that observed in subsequent cryo-EM structures or more rigorous MD simulations …”
Section: Identification Of the Cannabinoid Binding Site And First Str...contrasting
confidence: 66%
“…Auspiciously, a combination of docking and MD simulations from the hGlyR-α3 crystal structure could accurately predict the global orientation of THC in the Ser296 binding site, 33 in a similar position to that observed in the cryo-EM structures. Only slight differences from the cryo-EM model are observed, especially concerning various Phe residues interacting with the THC aromatic ring, which opens new research directions.…”
Section: Final Remarksmentioning
confidence: 69%
See 3 more Smart Citations